Peluang Pelaksanaan dan Tantangan Pengembangan Hospital without Walls pada Pelayanan Kebidanan dan Kandungan di RSUD Noongan - Mewengkang, Mario L.; Ratag, Gustaaf A. E.; Posangi, Jimmy (Universitas Sam Ratulangi, 2021)
Abstract: Hospitals as the health referral facilities play an important role in decreasing the maternal mortality rate (MMR) since they also belong to the personal health service as a whole including mother child health care. This study was aimed to analyze the implementation opportunities and challenges of developing ‘hospital without walls’ program in obstetrics and gynaecology services at RSUD (Rumah Sakit Umum Daerah) Noongan. This was a qualitative study. Informants in this study were taken from three places, as follows: the hospital, namely the Director of the Hospital and obstetrician-gynaecologist doctors; puskesmas (primary health center), namely the heads of puskesmas; and the community. Data were collected through in-depth interviews and direct observation. The results indicated that ‘hospital without walls’ in obstetrics and gynaecology services at RSUD Noongan had the opportunity to be implemented because this program had been partly applied by the hospital and it had a good impact on the hospital, health center, and the community as well as PONED-PONEK collaboration. The challenges of imple-menting this program at RSUD Noongan were the existence of cold cases caused by gatekeeper failure, lack of health facilities and human resources at the puskesmas, and insubstantial collaboration between PONED-PONEK. In conclusion, ‘hospital without walls’ program in obste-trics and gynaecology services can be implemented at RSUD Noongan with awareness to the possible challenges in its development.Keywords: opportunity and challenge; hospital without walls; obstetrics and gynecology services Abstrak: Rumah sakit sebagai fasilitas kesehatan rujukan paripurna berperan penting dalam menurunkan angka kematian ibu (AKI) termasuk pelayanan kesehatan ibu dan anak (KIA). Penelitian ini bertujuan untuk menganalisis peluang pelaksanaan dan tantangan pengembangan program hospital without walls pada pelayanan kebidanan dan kandungan di RSUD Noongan. Jenis penelitian ialah kualitatif. Informan penelitian diambil dari tiga tempat yaitu: RSUD Noongan (Direktur Rumah Sakit dan dokter spesialis obstetri dan ginekologi); puskesmas (kepala puskesmas); dan masyarakat. Data dikumpulkan melalui wawancara mendalam dan observasi langsung. Hasil penelitian memperlihatkan bahwa hospital without walls pada pelayanan kebi-danan dan kandungan di RSUD Noongan berpeluang untuk dilaksanakan karena sebagian pro-gram ini telah diterapkan oleh rumah sakit dan juga berdampak baik bagi rumah sakit, puskesmas dan masyarakat, serta kolaborasi PONED-PONEK. Tantangan pelaksanaan program ini di RSUD Noongan yaitu adanya cold case yang merupakan kegagalan gatekeeper, fasilitas kesehatan dan sumber daya manusia (SDM) yang masih kurang di puskesmas, serta kolaborasi PONED-PONEK belum optimal. Simpulan penelitian ini ialah program hospital without walls pada pelayanan kebidanan dan kandungan berpeluang untuk dilaksanakan di RSUD Noongan dengan memperhatikan tantangan pengembangan.Kata kunci: peluang dan tantangan; hospital without walls; pelayanan kebidanan dan kandungan